Integrated structural health monitoring for load detection using modern NDT techniques - Seah, Wen Fang (2018)
All structures, including critical civil infrastructure facilities like bridges and tunnels, deteriorate with time due to numerous reasons such as fatigue failure caused by repetitive loads and effects of environmental conditions. As a result, Structural Health Monitoring (SHM) is emerging as an important aspect for sustainable management of infrastructure systems, through continuous monitoring of a structure to provide an appraisal of changes as a function of time and serves as an early warning of an unsafe condition using real-time data. It involves the integration of sensors, data transmission and processing ability inside the structure. Nonetheless, extant non-destructive SHM techniques such as Lamb waves propagation and Electro-Mechanical Impedance (EMI) techniques can enhance the efficiency of damage detection through amalgamation. In this venture, Lamb waves propagation technique was further explored. Lamb waves are produced by pulsed ultrasound generated using a piezoelectric actuator to acquire information of the host structure though piezoelectric sensor. Lamb waves are known to be a surface wave, but recent finding claims that Lamb waves are spherical waves that have air-surface and air-air properties. This is expected to be advantageous when executing SHM in inaccessible areas. EMI and Lamb waves propagation techniques were integrated together to determine discontinuity in structures and amplify the results to achieve effective SHM. Hence, more experiments were carried out to substantiate this discovery and how structures of different dimensions give different waveforms. Statistical analysis in the form of transient energy was conducted to relate the damage severity with varying gap distance and the distance between the sensor and actuator.